2009
DOI: 10.1097/wnf.0b013e31817e08c3
|View full text |Cite
|
Sign up to set email alerts
|

Yi-Gan San as Adjunctive Therapy for Treatment-Resistant Schizophrenia

Abstract: In this open-label pilot study, patients treated with YGS showed a statistically significant reduction on clinician-rated scales. The present findings suggest that an adjunction of YGS might be effective for treatment-resistant schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 9 publications
1
45
1
Order By: Relevance
“…In clinical studies in Japan, where granules are commonly used, dosages of 6.0-9.0 g were applied [13][14][15][16]. The daily dosage in our sample was higher when the practitioner was of Asian origin compared to non-Asian origin.…”
Section: Discussionmentioning
confidence: 96%
“…In clinical studies in Japan, where granules are commonly used, dosages of 6.0-9.0 g were applied [13][14][15][16]. The daily dosage in our sample was higher when the practitioner was of Asian origin compared to non-Asian origin.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, clinical trials have demonstrated that yokukansan improves the behavioral and psychological symptoms of dementia (BPSD), i.e., aggressiveness, agitation, anxiety, hallucination, sleep disturbance, and psychotic disorders, which are observed in several types of dementia including Alzheimer's disease, without serious adverse effects (Hayashi et al, 2010;Iwasaki et al, 2005;Monji et al, 2009;Matsuda et al, 2013). In addition, this medicine has been shown to be effective for positive and negative symptoms including hallucination, delusion, excitement, and autism in drug-resistant schizophrenia patients (Miyaoka et al, 2009) and for hallucination, abnormal speech and behavior, and anger in post-operative delirium patients (Kurauchi, 2010). These clinical findings suggest that one common pharmacological property of yokukansan is an anti-psychotic action such as anti-hallucination and anti-delusion.…”
Section: Introductionmentioning
confidence: 98%
“…When taken in a cross-over manner, two Chinese medicines, Yi-Gan San (YGS) and Chaihu-Jia-Longgu-Muli Tan (CLMT), effected a decrease in HD symptoms in four HD patients (Satoh et al, 2009). In earlier studies, YGS was found to be effective in clinical trials involving patients suffering from dementia (Iwasaki et al, 2005), schizophrenia (Miyaoka et al, 2009), borderline personality disorder (BPD) and tardive dyskinesia (TD) . Saponins extracted from CLMT were reported as effective against depression and chronic mild stress-induced apoptosis in vivo (Zhu et al, 2006, Liu et al, 2010.…”
Section: Anti-hd Activity Of Herbal Formulationsmentioning
confidence: 95%